Corrosion detection method for zinc slag in hot galvanizing zinc liquid
During the detection of zinc slag in hot-dip galvanized zinc liquid, water is added during polishing, and the chemical reaction between zinc and water is used to achieve metallographic corrosion effect, which solves the problem of overcorrosion in the prior art and improves detection accuracy and efficiency.
Patent Information
- Application Number
- CN202411696335.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-03-18
AI Technical Summary
In the prior art, when detecting zinc slag in zinc liquid, it is easy to overcorrode due to the difficulty of mastering the acid corrosion liquid, which affects the accuracy of the zinc liquid quality detection results.
A corrosion detection method for zinc slag in hot-dip galvanized zinc liquid is adopted. By adding water during the polishing process, the chemical reaction between zinc and water is used to achieve metallographic corrosion effect without the need for the use of acid corrosion liquid.
This method effectively avoids overcorrosion, improves the accuracy of zinc liquid quality detection, is low cost and low risk, saves sample preparation time and reagent cost, and improves the efficiency of zinc liquid quality detection in the production process of galvanized automobile outer plates.
Smart Images

Figure CN119643546A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metallographic analysis of metal samples, and in particular to a corrosion detection method for zinc slag in hot-dip galvanizing liquid. Background Art
[0002] The steel materials of automobile outer panels mainly include cold-rolled sheets, hot-dip galvanized sheets, electro-galvanized sheets, etc. Among them, hot-dip galvanized sheets are obtained by dipping cold-rolled sheets in molten zinc liquid. They not only have the excellent mechanical properties of cold-rolled sheets, but also significantly improve corrosion resistance and surface aesthetics. Therefore, they are widely used in automobile manufacturing.
[0003] When the sheet is galvanized, the zinc liquid often contains varying amounts of zinc slag. For hot-dip pure zinc, the zinc slag is mainly slag Fe2Al5, which is formed by the dissolution of steel, iron impurities in zinc ingots, and corrosion of the zinc pot. The density of the slag is lower than that of the zinc liquid, so it will float, but its floating speed is slow. Suspended in the zinc liquid, it will increase the viscosity of the zinc liquid, resulting in poor wettability, thus making the zinc coating thicker and more brittle, and it is easy to adhere to the zinc coating, affecting the surface quality of the hot-dip galvanized sheet. Therefore, it is particularly important to monitor the amount of zinc slag in the zinc liquid in a timely manner to ensure the quality of the hot-dip galvanized sheet as an automotive exterior panel.
[0004] At present, the method for detecting zinc slag in zinc liquid is mainly to observe the size and amount of suspended slag after sampling by corroding zinc liquid with acidic corrosive solution. For example, Chinese patent CN109487192A discloses a method for controlling zinc ash and pitting defects on the surface of galvanized automobile outer panel. The disadvantage of this method is that the concentration ratio of the corrosive solution used in zinc liquid sampling is difficult to control, and it is easy to cause over-corrosion such as local corrosion and blackening of the sample, thereby affecting the accuracy of the zinc liquid quality detection result. Summary of the invention
[0005] Aiming at the technical problem that over-corrosion is prone to occur when using acidic corrosive solution when detecting zinc slag in zinc liquid, which affects the accuracy of zinc liquid quality detection results, the present invention provides a corrosion detection method for zinc slag in hot-dip galvanizing zinc liquid, which does not require the use of acidic corrosive solution and only requires the addition of water during sample preparation and polishing to achieve a good metallographic corrosion effect.
[0006] The technical solution of the present invention is: A method for detecting corrosion of zinc slag in hot-dip galvanizing zinc liquid comprises the following steps: longitudinally cutting a block sample of zinc liquid obtained after sampling and cooling the zinc liquid to expose a polished surface; polishing the polished surface using a polishing machine, adding water during the polishing process, with a water flow rate of 100-500 mL / min, maintaining the temperature at 20-60°C during polishing, and determining zinc liquid defects in the middle and upper areas of the polished surface under a microscope after polishing.
[0007] Furthermore, the zinc solution was sampled every 4 hours.
[0008] Furthermore, the scum on the surface of the zinc liquid is scraped off before sampling, and the sampler is inserted 1 meter below the surface of the zinc liquid, and begins sampling after being rinsed three times in the zinc liquid.
[0009] Furthermore, the polishing machine is an electric metallographic polishing machine.
[0010] Furthermore, the rotation speed of the electric metallographic polishing machine is 800-850 rpm.
[0011] Furthermore, the water added during the polishing process is deionized water to prevent impurities in the water from contaminating the polishing surface.
[0012] Furthermore, the microscope is an optical microscope.
[0013] Furthermore, the observation area of the microscope is 10 mm 2 .
[0014] Furthermore, the criteria for judging zinc slag in zinc liquid include: 2 When there is zinc slag with a size greater than 100 μm in the area, the zinc liquid cannot be used as raw material for the production of galvanized automobile outer panels.
[0015] Furthermore, the criteria for judging zinc slag in zinc liquid include: 2 When there are zinc slag with a size larger than 100μm in the area, the zinc slag density exceeds 30 pieces / 10mm 2 , zinc liquid cannot be used as raw material for the production of galvanized automobile exterior panels.
[0016] The beneficial effects of the present invention are: The present invention provides a corrosion detection method for zinc slag in hot-dip galvanized zinc liquid. It does not need to use conventional acidic corrosive liquid to metallographically corrode the sample. Instead, water is added during polishing to generate heat by friction under certain conditions. Zinc, as a metal with relatively active chemical properties, reacts with water (Zn+2H2O=Zn(OH)2+H2), while zinc slag (Fe2Al5) is chemically stable and does not react with water, which makes the boundary of zinc slag obvious, and the chemical corrosion effect of the metallographic sample is good, and there will be no over-corrosion. Moreover, the corrosion detection method provided by the present invention uses only water as a reagent, which is low in cost and low in danger, saves sample preparation time and reagent costs, completes sample metallographic corrosion while polishing, and also improves the efficiency of zinc liquid quality detection in the production process of hot-dip galvanized automobile outer panels. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0018] Figure 1 This is a schematic diagram of the longitudinal cutting of a zinc liquid block sample.
[0019] Figure 2 It is a schematic diagram of the location of the observation area on the polished surface.
[0020] Figure 3 This is a microscope image of Example 1.
[0021] Figure 4 This is the microscope image of Comparative Example 1.
[0022] In the figure, 1-cutting surface, 2-zinc liquid block sample, 3-observation area, 4-polished surface. DETAILED DESCRIPTION
[0023] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0024] Example 1 A method for detecting corrosion of zinc slag in hot-dip galvanizing zinc liquid comprises the following steps: (1) It is planned to produce 290 tons of galvanized automobile outer panel IF steel DX53D+Z. The zinc liquid is sampled every 4 hours. In this embodiment, the zinc liquid in the zinc pot is sampled when 60 tons are produced. Before sampling, the scum on the surface of the zinc liquid is scraped off to avoid the scum affecting the sampling results. The sampler is inserted below 1 meter below the zinc liquid surface. After being rinsed in the zinc liquid three times, sampling begins; (2) The taken-out zinc liquid is cast into a mold, and cooled and solidified at room temperature to obtain a zinc liquid block sample; (3) Cut the zinc liquid block sample longitudinally (such as Figure 1As shown in the figure, the reason for longitudinal cutting is that the density of zinc slag is lower than that of zinc, so it will float on the surface of zinc liquid. After the zinc liquid cools and solidifies, the zinc slag is concentrated on the upper surface of the zinc liquid block sample. In addition, due to tension when the zinc liquid solidifies, the upper surface of the zinc block is generally concave, and it is difficult to polish and observe directly from the upper surface. Therefore, longitudinal cutting is selected to observe the area close to the upper surface). After the polished surface is exposed, an electric metallographic polishing machine is used for polishing; the speed of the electric metallographic polishing machine is 850 revolutions per minute. Deionized water is added during the polishing process, and the flow rate of deionized water is 500mL / minute. The temperature is maintained at 20-60℃ during polishing (if the temperature is too low, it is difficult for water to react with zinc, and if the temperature is too high, the operator is easily scalded); due to the relatively active chemical properties of zinc, friction generates heat and reacts with water during the polishing process (Zn+2H2O=Zn(OH)2+H2), making the boundary of the zinc slag obvious, achieving the same effect as chemical corrosion of the metallographic sample; (4) After water polishing, the polished surface is gray and smooth. From the middle and upper area of the polished surface (close to the upper surface of the zinc liquid block sample obtained in step (2), Figure 2 Select 10mm for the observation area shown) 2 Observe and measure the size and density of zinc slag (dross) under an optical microscope. Figure 3 As shown, Figure 3 The image is clear, which is convenient for defect judgment. It is found that the size of zinc slag is about 20μm and the density of zinc slag is 10 / 10mm 2 , does not exceed the standard for judging zinc slag in zinc liquid (when 10mm 2 When zinc slag with a size larger than 100 μm is observed in the area, zinc liquid cannot be used as raw material for the production of galvanized automobile outer panels; when no 10 mm 2 When there are zinc slag with a size larger than 100μm in the area, the zinc slag density exceeds 30 pieces / 10mm 2 , zinc liquid cannot be used as raw material for the production of galvanized automobile outer panels), and the production of galvanized automobile outer panels can continue.
[0025] Example 2 A method for detecting corrosion of zinc slag in hot-dip galvanizing zinc liquid comprises the following steps: (1) It is planned to produce 310 tons of galvanized automobile outer panel BH steel HC220BD+Z. The zinc liquid is sampled every 4 hours. In this embodiment, the zinc liquid in the zinc pot is sampled when the production reaches 250 tons. Before sampling, the scum on the surface of the zinc liquid is scraped off to avoid the scum affecting the sampling results. The sampler is inserted below 1 meter below the zinc liquid surface. After being rinsed in the zinc liquid three times, sampling begins; (2) The taken-out zinc liquid is cast into a mold, and cooled and solidified at room temperature to obtain a zinc liquid block sample; (3) Use a cutting blade to cut the zinc liquid block sample longitudinally (such as Figure 1As shown in the figure, the reason for longitudinal cutting is that the density of zinc slag is lower than that of zinc, so it will float on the surface of zinc liquid. After the zinc liquid cools and solidifies, the zinc slag is concentrated on the upper surface of the zinc liquid block sample. In addition, due to tension when the zinc liquid solidifies, the upper surface of the zinc block is generally concave, and it is difficult to polish and observe directly from the upper surface. Therefore, longitudinal cutting is selected to observe the area close to the upper surface). After the polished surface is exposed, it is polished using an electric metallographic polishing machine; the speed of the electric metallographic polishing machine is 800 revolutions per minute. Deionized water is added during the polishing process, and the flow rate of deionized water is 100mL / minute. The temperature is maintained at 20-60℃ during polishing (if the temperature is too low, it is difficult for water to react with zinc, and if the temperature is too high, the operator is prone to accidental contact and burns); due to the relatively active chemical properties of zinc, friction generates heat and reacts with water during the polishing process (Zn+2H2O=Zn(OH)2+H2), making the boundary of the zinc slag obvious, achieving the same effect as chemical corrosion of the metallographic sample; (4) After water polishing, the polished surface is gray and smooth. From the middle and upper area of the polished surface (close to the upper surface of the zinc liquid block sample obtained in step (2), Figure 2 Select 10mm for the observation area shown) 2 The size and density of zinc slag (dross) were observed and measured under an optical microscope. It was found that the size of zinc slag was about 50μm and the number of zinc slag was 35 / 10mm. 2 , exceeding the standard for judging zinc slag in zinc liquid (when no 10mm 2 When there are zinc slag with a size larger than 100μm in the area, the zinc slag density exceeds 30 pieces / 10mm 2 , zinc liquid cannot be used as raw material for the production of galvanized automobile outer panels), the operator then switched to inner panel IF steel DX52D+Z for production and carried out zinc pot slag removal operations.
[0026] In the subsequent production of inner panels, the amount of zinc slag on the panel surface gradually increased, and its surface quality could not meet the quality requirements of automobile outer panels. Timely switching of inner panels avoided the subsequent loss of outer panel qualification rate.
[0027] Example 3 A method for detecting corrosion of zinc slag in hot-dip galvanizing zinc liquid comprises the following steps: (1) When the production of automobile outer panel BH steel HC220BD+Z reached 250 tons in Example 2, zinc slag was sampled and tested in the zinc liquid, and it was found that the zinc slag exceeded the standard for judging zinc slag in the zinc liquid. The production of the inner panel DX52D+Z was switched to the zinc pot slag removal operation; after producing DX52D+Z steel and continuing to slag for 4 hours, the zinc liquid in the zinc pot was continuously sampled, and the slag on the surface of the zinc liquid was removed before sampling to avoid the slag affecting the sampling results. The sampler was immersed below 1 meter below the zinc liquid surface, and sampling began after being rinsed in the zinc liquid three times; (2) The taken-out zinc liquid is cast into a mold, and cooled and solidified at room temperature to obtain a zinc liquid block sample; (3) Use a cutting blade to cut the zinc liquid block sample longitudinally (such as Figure 1 As shown in the figure, the reason for longitudinal cutting is that the density of zinc slag is lower than that of zinc, so it will float on the surface of zinc liquid. After the zinc liquid cools and solidifies, the zinc slag is concentrated on the upper surface of the zinc liquid block sample. In addition, due to tension when the zinc liquid solidifies, the upper surface of the zinc block is generally concave, and it is difficult to polish and observe directly from the upper surface. Therefore, longitudinal cutting is selected to observe the area close to the upper surface). After the polished surface is exposed, it is polished using an electric metallographic polishing machine; the speed of the electric metallographic polishing machine is 800 revolutions per minute. Deionized water is added during the polishing process, and the flow rate of deionized water is 500mL / minute. The temperature is maintained at 20-60℃ during polishing (if the temperature is too low, it is difficult for water to react with zinc, and if the temperature is too high, the operator is prone to accidental contact and burns); due to the relatively active chemical properties of zinc, friction generates heat and reacts with water during polishing (Zn+2H2O=Zn(OH)2+H2), making the boundary of the zinc slag obvious, achieving the same effect as chemical corrosion of the metallographic sample; (4) After water polishing, the polished surface is gray and smooth. From the middle and upper area of the polished surface (close to the upper surface of the zinc liquid block sample obtained in step (2), Figure 2 Select 10mm for the observation area shown) 2 The size and density of zinc slag (dross) were observed and measured under an optical microscope. It was found that the size of zinc slag was about 25μm and the density of zinc slag was 22 pieces / 10mm. 2 , the zinc liquid condition improved, and then switched to outer plate production.
[0028] Comparative Example 1 A method for detecting corrosion of zinc slag in hot-dip galvanizing zinc liquid comprises the following steps: (1) It is planned to produce 200 tons of galvanized automobile outer panel BH steel HC180BD+Z. When the production reaches 120 tons, the zinc liquid in the zinc pot is sampled. Before sampling, the scum on the surface of the zinc liquid is scraped off to avoid the scum affecting the sampling results. The sampler is inserted below 1 meter below the zinc liquid surface and rinsed in the zinc liquid three times before starting sampling; (2) The taken-out zinc liquid is cast into a mold and cooled and solidified at room temperature to obtain a zinc liquid block sample; (3) Use a cutting blade to cut the zinc liquid block sample longitudinally to expose the polished surface, use an electric metallographic polishing machine to polish the polished surface, and then use 25% hydrochloric acid + 3.5g / L hexamethylenetetramine to corrode the polished surface; (4) Select a 10 mm thick section from the middle and upper area of the polished surface after corrosion (close to the upper surface of the zinc liquid block sample obtained in step (2)). 2 The size and density of zinc slag (dross) were observed and counted under an optical microscope. It was found that the size of zinc slag was about 100μm and the density of zinc slag was 50 pieces / 10mm.2 .
[0029] The etching solution of 25% hydrochloric acid + 3.5g / L hexamethylenetetramine is a stable and controllable etching solution formula obtained by operators through multiple experiments. It can clearly identify the zinc slag on the polished surface after etching. Figure 4 As shown in the figure, the polished surface after corrosion is locally corroded and turns black, and the over-corrosion black spots are similar in appearance to zinc slag, which greatly affects the judgment of defects. In addition, the preparation of the etching solution is also more troublesome and dangerous. It is better to directly add deionized water during polishing to save time and effort.
[0030] Although the present invention has been described in detail with reference to the accompanying drawings and in combination with the preferred embodiments, the present invention is not limited thereto. Without departing from the spirit and essence of the present invention, a person of ordinary skill in the art may make various equivalent modifications or substitutions to the embodiments of the present invention, and these modifications or substitutions shall be within the scope of the present invention. Any person of ordinary skill in the art may easily think of changes or substitutions within the technical scope disclosed by the present invention, and these shall be within the scope of protection of the present invention.
Claims
1. A method for detecting corrosion of zinc slag in hot-dip galvanizing liquid, characterized in that: The zinc liquid block sample obtained after the zinc liquid is sampled and cooled is cut longitudinally to expose the polished surface; the polished surface is polished with a polishing machine, water is added during the polishing process, the water flow rate is 100-500mL / min, the temperature is maintained at 20-60°C during polishing, and after polishing, the zinc liquid defects are judged in the middle and upper areas of the polished surface under a microscope.
2. The method for detecting corrosion of zinc slag in hot-dip galvanizing liquid according to claim 1, characterized in that: The zinc solution was sampled every 4 hours.
3. The corrosion detection method of zinc slag in hot-dip galvanizing liquid as claimed in claim 1, characterized in that: Before sampling, scrape off the scum on the surface of the zinc liquid, insert the sampler to less than 1 meter below the surface of the zinc liquid, rinse it in the zinc liquid three times and then start sampling.
4. The method for detecting corrosion of zinc slag in hot-dip galvanizing liquid according to claim 1, characterized in that: The polishing machine is an electric metallographic polishing machine.
5. A method for detecting corrosion of zinc slag in hot-dip galvanizing liquid as claimed in claim 4, characterized in that: The speed of the electric metallographic polishing machine is 800-850 rpm.
6. A method for detecting corrosion of zinc slag in hot-dip galvanizing liquid as claimed in claim 1, characterized in that: The water added during the polishing process is deionized water.
7. The method for detecting corrosion of zinc slag in hot-dip galvanizing liquid according to claim 1, characterized in that: The microscope is an optical microscope.
8. The method for detecting corrosion of zinc slag in hot-dip galvanizing liquid according to claim 1, characterized in that: The observation area of the microscope is 10 mm 2 .
9. The method for detecting corrosion of zinc slag in hot-dip galvanizing liquid according to claim 1, characterized in that: The criteria for judging zinc slag in zinc liquid include: 2 When there is zinc slag with a size greater than 100 μm in the area, the zinc liquid cannot be used as raw material for the production of galvanized automobile outer panels.
10. The method for detecting corrosion of zinc slag in hot-dip galvanizing liquid according to claim 1, characterized in that: The criteria for judging zinc slag in zinc liquid include: when no 10mm 2 When there are zinc slag with a size larger than 100μm in the area, the zinc slag density exceeds 30 pieces / 10mm 2 , zinc liquid cannot be used as raw material for the production of galvanized automobile exterior panels.
Citation Information
Patent Citations
Method for controlling zinc ash and pitting defects on surface of galvanized automobile outer plate
CN109487192A